Barrister's Hall, Pemberton Square, n.d. - Unknown (Tufts Archival Research Center, 2005)
Elevated view looking towards the upper stories of Barrister's Hall in Pemberton Square. Two retracted awnings are seen in the view as well as several air conditioning units in the windows on the upper floors. 11 7/16 x 10 13/16 overall 13 7/8 x 11 Photographs